Synthesis Characterization and Nuclease Activity of some Novel Palladium II Complexes of Benzil Thiosemicarbazone BTSC and Substituted Thiosemicarbazones - Kinthada, Dr Prakash MMS (International Journal of Pharmaceutical & Biological Archive, 2012)
Synthesis Characterization and Nuclease Activity of some Novel Palladium II Complexes of Benzil Thiosemicarbazone BTSC and Substituted Thiosemicarbazones